Pengaruh kebijakan Financing to Value dan faktor ekonomi terhadap pembiayaan pemilikan rumah di bank syariah - Anggi Aprian Syaputra; Achmad Tohirin (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The high rate of population growth has an impact on increasing demand for one of their homes. This study aims to examine the effect of financing to value policies, non-performing financing, third party funds, population growth, and inflation on sharia home ownership financing in Islamic banks. This research is focused on sharia commercial banks and sharia business units in Indonesia which are listed on the BI and OJK websites for the period 2010-2018. This research will be analyzed using Error Correction Model (ECM). The software used in this study is Microsoft Excel 2010 and Eviews 9 program. The results of the study show that the variables ftv, npf, and dpk have a positive effect. While the variables of economic growth and inflation have a negative effect on housing finance.